A comparison Of Some Semiparametric Estimators For consumption function Regression - حمود, مناف يوسف; عيسى, اسيل مسلم (Journal of Economics and Administrative Sciences, 2012)
This article aims to explore the importance of estimating the a semiparametric regression function ,where we suggest a new estimator beside the other combined estimators and then we make a comparison among them by using simulation technique . Through the simulation results we find  that the suggest estimator is the best with the first and second models ,wherealse for the third model we find Burman and Chaudhuri (B&C) is best.